Rancang Bangun Prototipe Kapal Katamaran Glass Bottom Ekowisata Laut - Yunianto, Anton Hekso; Kusuma, Hollanda Arief (Sustainable, 2023)
A glass-bottom catamaran is a vessel with two hulls with a layer of glass at the bottom of the boat, allowing passengers to view underwater scenery. This research focused on the planning stage in designing a prototype of a glass bottom catamaran, intending to determine the optimal main dimensions and produce a high-quality vessel. The results showed that determining the main dimensions of the prototype vessel is highly influenced by the aspect ratio, particularly the L/B ratio. This ratio is used as a reference in designing the prototype vessel as it affects vessel parameters such as resistance, maneuverability, and cost. Additionally, dividing the process of manufacturing the prototype vessel into several stages, including conceptual design, system design, structural design, steering system design, and electrical system design, is crucial to ensure the quality and safety of the prototype vessel. The visual depiction of the shape and characteristics of the glass bottom catamaran prototype indicates that the prototype vessel has two demi hulls and an asymmetrical hull shape..